A Broadband Ultrafast Transient Absorption Spectrometer Covering the Range from Near-Infrared (NIR) down to Green. Issue 10 (October 2014) - Schmidhammer, Uli; Jeunesse, Pierre; Stresing, Gerhard; Mostafavi, Mehran
We present a new development for pump–probe absorption spectroscopy that allows the simultaneous measurement from the green part of the visible spectrum (510 nm) over the whole near-infrared range to >1600 nm, corresponding to 0.77-2.40 eV. The system is based on a sub-picosecond supercontinuum generated in bulk material used as a broadband probe that is dispersed with a custom-made prism spectrometer and detected by an InGaAs array with extended sensitivity to the visible. Two versions, with and without probe referencing, are implemented for operation at laser repetition rates of a few hertz and kilohertz, respectively. After presentation of the optical configuration of the spectrometer, its performance is characterized and further illustrated on two time scales, with the ultrafast radiolysis of isopropanol induced by a picosecond electron pulse and with the instantaneous response of a BK7 plate to a femtosecond light pulse. The photophysics of the dye IR-140 is resolved from the femto- to picosecond regime. Stable and easy day-to-day routine use of the spectrometer also can be achieved in non-optical laboratory surroundings. For operation in a hazardous environment, the optical probe beams can be transported to the detector unit by optical fibers.